Analysis of Spatial Distribution of Climatic Comfort Conditions in Diyarbakır City - Murat Türkeş; Savaş Çağlak (Journal of Advanced Research in Natural and Applied Sciences)
Cities have more adverse thermal comfort conditions than the rural and semi-rural areas around them. In this study, it is aimed to examine the spatial distribution of thermal comfort conditions in Diyarbakir, a historical city in the Southeastern Anatolia Region of Turkey. Thermal comfort can be defined as the state of people feeling comfortable or happy in their environment or thermal environment. Uncomfortable conditions lead to social, economic and physical negativities, especially to human health. Thermal comfort conditions were calculated with the Physiological Equivalent Temperature index obtained from the RayMan model using hourly measurement data for the 2015 – 2021 (7 years) period of four meteorological stations in the field. In the study, while 'cold' and 'cool' stresses are experienced in the winter season in Diyarbakır, 'warm', 'hot' and 'very hot' stresses were determined in the 5-month hot period of the year (May-September). Evaluations revealed that densely built urban areas in the city center (approximately 15%) have more unfavourable thermal conditions than low-density urban areas (approximately 30%) and rural areas (approximately 20%) around them. It is a vital necessity to design and plan with a contemporary smart geographical perspective to reduce the negative thermal conditions of cities and for sustainable healthy cities.